Aryl sulfonyl chlorides and sodium aryl sulfinates: non-volatile, non-stench, and non-toxic aryl thiol surrogates for direct aryl-sulfenylation of C–H bonds. (3rd March 2020) - Lu, Xiaohui; Yi, Qicheng; Pan, Xicai; Wang, Peifang; Vessally, Esmail
ABSTRACT: Aryl sulfonyl chlorides and sodium aryl sulfinates are proved to be powerful arylating agents for the C–C bonds formation through desulfitative cross-coupling reactions. These versatile compounds have also been widely utilized as aryl sulfonyl sources in the synthesis of aromatic sulfones. As evidenced in the literature, aryl sulfonyl chlorides and sodium aryl sulfinates are also promising sulfenylation agents for the efficient and practical construction of synthetically and medicinally important aryl thioethers (through the cleavage of their sulfur–oxygen and sulfur–chloride/oxygen-sodium bonds). In this focus review, we have summarized recent progress and developments in the direct sulfenylation of C–H bonds utilized the titled compounds with special emphasis on the mechanistic aspects of the reactions. GRAPHICAL ABSTRACT: